Three‐phase four‐dimensional computed tomography as a first‐line investigation in primary hyperparathyroidism. Issue 9 (12th May 2021) - Leong, David; Ng, Katrina; Boeddinghaus, Rudolf; Lisewski, Dean
Abstract: Introduction: Parathyroid computed tomography using multiple phases (four‐dimensional computed tomography (4DCT) for parathyroid localization was first described in 2006. Since its inception, there has been variable uptake of this technique due to inconsistency of results between institutions and perceived higher radiation dose than technetium‐99 sestamibi scans (MIBI). 4DCT has been the primary imaging modality for parathyroid localization at our institution since 2013. Methods: A retrospective study of surgically managed patients with primary hyperparathyroidism who had preoperative localization with 4DCT from 2013–2018 was performed. Results: A total of 353 patients were included for analysis. The positive predictive value (PPV) of our three‐phase 4DCT protocol was 93.3%, sensitivity (localized) 85.2% with a 5.8% false‐positive rate and 13.9% false‐negative (non‐localizing) rate when reported by a head and neck radiologist (HNR). Calculated effective dose varied from 4.5 to 8.9mSV. On multivariable logistic regression, reporting by an experienced HNR ( P  < 0.001) and gland weight > 200 mg ( P  = 0.002) were significant for higher accuracy, lower false positives and false negatives. Conclusion: A first‐line three‐phase 4DCT protocol for primary hyperparathyroidism is an accurate technique providing precise anatomical localization of abnormal parathyroid glands, particularly when performed by a specialist HNR. In our practise, it provides the best rate of detection and superior anatomical localization needed for minimally invasive parathyroid surgery, compared to other commonly used localization techniques. It also avoids the need for four gland exploration in the majority of patients with primary hyperparathyroidism. Abstract : Three phase four‐dimensional computed tomography as a first line investigation modality in primary hyperparathyroidism provides rapid and accurate anatomical localisation with acceptable radiation dosing.